The seascape discourse in H. Heine’s collection of poems “Neue Gedichte” - Ніколенко, Катерина Сергіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article deals with the seascape discourse in H. Heine’s collection of poems “Neue Gedichte” (1844). The article provides a detailed analysis of the chief concepts, themes, motives, imagery, symbols which define the seascape discourse, of the lyrical hero’s character in “Neue Gedichte” and of the poetical peculiarities related to the seascape discourse.The concepts of soul, life, nature, God are central to H. Heine’s book and are expressed through the motives of spleen, anguish, and lyrical hero’s pensive moods. While overcoming the vicissitudes of life, H. Heine’s lyrical hero experiences personal growth, ponders over his existence and environment in a wide cultural and historical context. The seascape and other related imagery (waves, a deep torrent, a seagull, blue thoughts etc) reveal the lyrical hero’s rich inner life, his romantic reservations and a search for unity with nature and the world.As the lyrical plot progresses, the seascape is reconsidered by the poet and acquires a whole complex of diverse meanings, which lead to a growing scope of related themes (love, death, afterlife), motives (blood, light, music), imagery (waves, seagulls, mermaid), symbols (stars, the sun, a stormy torrent). Based on the original text of the book, the chief art tools which define the seascape discourse have been described: numerous repetitions, synonyms, binary oppositions, contrasts, symbols.